Progress in the development of fatty acid synthase inhibitors as anticancer targets. Issue 20 (15th October 2015) - Mullen, Genevieve E.; Yet, Larry
Graphical abstract: Abstract: Fatty acid synthase (E.C. 2.3.1.85; FASN) is a multifunctional enzyme system that catalyzes the formation of fatty acids from acetyl-CoA, malonyl-CoA, and NADPH and plays a central role in lipid biosynthesis. Two classes of FASN exist: FASN I in animals and fungi, and FASN II in plants and prokaryotes. Animal FASN I is a homodimeric protein found in the cytosol of lipogenic tissues such as the liver and brain. Many human carcinomas exhibit elevated levels of FASN I, though the benefit to cancer cells is still unclear. Inhibition of FASN I selectively effects apoptosis in cancer cells, and the role of FASN I in chemotherapy is a growing area of research with the use of natural products and small molecule inhibitors.